2020
DOI: 10.1016/j.neuron.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Outcome Representation in the Primary Motor Cortex

Abstract: Highlights d Populations of layer 2-3 pyramidal neurons in M1 report motor performance outcome d Success and failure activity is late, prolonged, and dissociated from kinematics and reward d At trial start, layer 5 pyramidal tract activity is affected by previous outcome d Post-movement activity in M1 is required for motor performance and learning

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 116 publications
6
99
0
Order By: Relevance
“…Consistent with a dissociable role of reinforcement and reward in motor learning, previous research has shown that certain subpopulations of neurons in the motor cortex ( i.e. , a key region of the motor learning network; Krakauer et al, 2019) are responsive to the outcome of previous movements irrespective of reward (Levy et al, 2020), while others respond to reward regardless of the previous outcome (Ramkumar et al, 2016). Put together, these elements indicate that estimating the net impact of reward on motor learning requires controlling for the effect of the reinforcement feedback on the learning process.…”
Section: Introductionmentioning
confidence: 72%
“…Consistent with a dissociable role of reinforcement and reward in motor learning, previous research has shown that certain subpopulations of neurons in the motor cortex ( i.e. , a key region of the motor learning network; Krakauer et al, 2019) are responsive to the outcome of previous movements irrespective of reward (Levy et al, 2020), while others respond to reward regardless of the previous outcome (Ramkumar et al, 2016). Put together, these elements indicate that estimating the net impact of reward on motor learning requires controlling for the effect of the reinforcement feedback on the learning process.…”
Section: Introductionmentioning
confidence: 72%
“…Volitional forelimb movements are thought to be represented by relatively dense activity patterns in both superficial and deep layers of motor cortex (Dacre et al, 2019;Estebanez et al, 2017;Hira et al, 2013;Isomura et al, 2009;Levy et al, 2020;Park et al, 2019;Sauerbrei et al, 2019;Wang et al, 2017), but whether these patterns represent specific actions (Galiñanes et al, 2018) or a more generalised motor signal (Kaufman et al, 2016) remains unresolved. By combining population imaging with single neuron / population-based classifiers and dimensionality reduction in mice, we find that most layer 5B neurons display actioninvariant signalling, while action-specific representations are restricted to sparse, spatially heterogeneous subpopulations of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, volitional forelimb movements such as reach-to-grasp (Estebanez et al, 2017;Galiñanes et al, 2018;Guo et al, 2015;Levy et al, 2020;Sauerbrei et al, 2019;Wang et al, 2017) or pulling / pushing a grasped lever (Dacre et al, 2019;Hira et al, 2013;Isomura et al, 2009;Miri et al, 2017;Morandell and Huber, 2017;Park et al, 2019) have been associated with widespread, bidirectional neuronal modulation in both superficial and deep layers of sensorimotor cortex, driven by long-range inputs from motor thalamus (Dacre et al, 2019;Sauerbrei et al, 2019;Tanaka et al, 2018). Both excitatory and inhibitory neurons display dense task-related activity which emerges across learning and correlates with enhanced limb coordination (Hwang et al, 2019;Laubach et al, 2000;Masamizu et al, 2014;Peters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations